Case study of noise attenuation of large automotive manufacturing facility - Novak, Colin (Canadian Acoustics, 2002)
This case study reports on the efforts taken to significantly attenuate the overall noise exposure on several residential receptors from the operations of a large scale automotive manufacturing facility. The exercise began with an extensive noise survey of the facility to identify the significant noise contributors followed by the modeling of the noise propagation from these sources. Noise abatement measures were then modeled to predict attenuation values at the receptors which were then compared to legislated acceptable levels. A noise abatement plan was created along with a schedule to facilitate the attenuation recommendations. While not complete, the measures implemented thus far have exceeded all expectations.